Authormagic - An Approach to Author Disambiguation in Large-Scale Digital Libraries - Weiler, Henning; Meyer-Wegener, Klaus; Mele, Salvatore (Proc. 20th ACM Conf. on Information and Knowledge Management, 2011)
A collaboration of leading research centers in the field of High Energy Physics (HEP) has built INSPIRE, a novel information infrastructure, which comprises the entire corpus of about one million documents produced within the discipline, including a rich set of metadata, citation information and half a million full-text documents, and offers a unique opportunity for author disambiguation strategies. The presented approach features extended metadata comparison metrics and a three-step unsupervised graph clustering technique. The algorithm aided in identifying 200'000 individuals from 6'500'000 author signatures. Preliminary tests based on knowledge of external experts and a pilot of a crowd-sourcing system show a success rate of more than 96% within the selected test cases. The obtained author clusters serve as a recommendation for INSPIRE users to further clean the publication list in a crowd-sourced approach. © 2011 ACM.
UnivIS-Import:2015-04-16:Pub.2011.tech.IMMD.IMMD6.author
Keywords: author disambiguation; digital libraries; entity resolution; knowledge management